1999
DOI: 10.1002/(sici)1097-4652(199910)181:1<33::aid-jcp4>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Steps in integrin β1‐chain glycosylation mediated by TGFβ1 signaling through ras

Abstract: Ras is activated by transforming growth factor beta (TGFbeta) in several cell types, but the biological consequences of this activation are largely unknown. We now show that ras mediates two stages in integrin beta1-chain maturation: 1) glycosylation of the 86-kD core peptide, which is a TGFbeta1-independent process, and 2) TGFbeta1-mediated conversion of the 115-kD beta1 integrin precursor into the mature 130-kD form. HD3 colon epithelial cells maintain elevated levels of integrin alpha2beta1 heterodimers, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 47 publications
3
19
1
Order By: Relevance
“…The TGF-␤1/Ras pathway functions to convert a partially glycosylated ␤ 1 integrin precursor into the mature, fully glycosylated form and is blocked by dominant-negative N17Ras (58). In like fashion, constitutive activation of Ki-Ras in stable oncogenic Ki-ras transfectants may up-regulate glycosyltransferases that modify T␤RIII.…”
Section: Antisense Oligonucleotides To Ki-ras Decrease Post-translatimentioning
confidence: 86%
See 1 more Smart Citation
“…The TGF-␤1/Ras pathway functions to convert a partially glycosylated ␤ 1 integrin precursor into the mature, fully glycosylated form and is blocked by dominant-negative N17Ras (58). In like fashion, constitutive activation of Ki-Ras in stable oncogenic Ki-ras transfectants may up-regulate glycosyltransferases that modify T␤RIII.…”
Section: Antisense Oligonucleotides To Ki-ras Decrease Post-translatimentioning
confidence: 86%
“…In this study, we have shown that both functional, posttranslationally modified T␤RIII and the biological response to TGF-␤1 were restored by stable expression of oncogenic Ki- (58). The TGF-␤1/Ras pathway functions to convert a partially glycosylated ␤ 1 integrin precursor into the mature, fully glycosylated form and is blocked by dominant-negative N17Ras (58).…”
Section: Antisense Oligonucleotides To Ki-ras Decrease Post-translatimentioning
confidence: 99%
“…The hypoglycosylated form (lower band in Fig 4C) was tentatively identified as biosynthetic precursor of 1 subunit. The band with lower migration rate (upper band in Fig 4C) was the hyperglycosylated mature form of integrin 1 subunit, which mainly located at the plasma membrane [21][22][23]. The correlation between 5 1 integrin and cell migration has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…9C). It was reported that the higher molecular weight form represents the mature form of ␤1 integrin (42). Two differently glycosylated forms of ␤1 integrin resolved to one lower molecular weight band after N-glycanase treatment (Fig.…”
Section: Forced Expression Of Core3 Synthase Decreases Prostate Cancementioning
confidence: 99%